Palliative cytoreduction with low dose intravenous melphalan in patients with acute myeloid leukemia refractory to prior treatment. Issue 1 (2nd January 2022) - De Backer, Eva; Deeren, Dries
ABSTRACT: Background: Hyperproliferative crises with hyperleukocytosis occur frequently in the disease course of refractory or relapsed acute myeloid leukemia (AML). Palliative cytoreduction aims to control blast count in order to avoid life-threatening complications and preserve quality of life in patients unfit for intensive treatment. In our center, low-dose intravenous melphalan is sometimes used with this intent. Methods: We performed a retrospective analysis of patients with AML who were treated with low-dose intravenous melphalan (15–30 mg/m 2 ) in a palliative setting. Results: Thirty patients with AML who received low-dose melphalan (15–25 mg/m 2 ) were identified. In total, 63 administrations of low-dose melphalan were counted. A clear cytoreductive effect (>50%) was seen within a few days in 78% of melphalan administrations. The median duration of response after an individual dose was 17 days (interquartile range [IQR] 10–26). The median overall survival was 29 days (IQR 16–73). Most common side effects were worsening pancytopenia with neutropenic fever and an increase in transfusion dependency and tumor lysis syndrome. Conclusion: Intravenous low-dose melphalan is effective, quick and safe as palliative cytoreductive therapy in patients with hyperproliferative AML. It can be considered in palliative care of patients refractory to prior treatment with preserving acceptable quality of life. Our small retrospective cohort is the first to report the use of low-dose intravenous melphalan as palliative cytoreductive treatment in this population.